(untitled) (Research, Society and Development, 2020)
Nowadays, the world’s plastic production generates lot of plastic waste. Therefore, the need of reducing conventional nonbiodegradable plastic materials has encouraged the development of innovative biodegradable materials from renewable resources. Biobased polymer film can be developed using naturally occurring sources like polysaccharides, proteins, lipids, and their combinations. Natural edible polymers are the materials made from natural edible constituents that can be consumed by animals or human beings with no health risk. Also, there are additives that could be used as well to improve the package characteristics, such as essential oils, antioxidants. This review article aims to make an extensive literature review and compare data found by several authors in relation to the various natural polymers used in the manufacture of edible coatings and films applied in food products, and thereby show that their use can improve their characteristics and prolong the shelf life. More than 130 bibliographic references were used to produce this review article and several research platforms were used (Scielo, google academic, among others). After the extensive literature review, it is possible to conclude that the use of polymers obtained from natural sources is effective for preserving food for a longer time and thus causing a reduction in the loss of shelf life in these products.